STRATEGI PENGEMBANGAN KAWASAN WISATA DIENG BERBASIS LOCAL WISDOM (Studi Event Dieng Culture Festival) - Nugroho, Dwi Yoso; Subeni, Fajar; Suswanto, Suswanto (Pringgitan, 2023)
This research aims to explore the development strategy of the Dieng tourism area based on local wisdom, with a specific focus on the Dieng Culture Festival. The study employs a qualitative approach to delve into the perspectives of the local community and to gain an in-depth understanding of the underlying local wisdom. Through a combination of observation, in-depth interviews, and document analysis, data were collected from various stakeholders including local residents, tourism practitioners, governmental authorities, academics, and participants of the Dieng Culture Festival. The research begins with a comprehensive literature review on local wisdom, sustainable tourism development, cultural event tourism, community participation, and socio-cultural-economic impacts. Findings reveal intricate connections between local wisdom, the Dieng Culture Festival, and the overall development of the tourism area. Furthermore, the study evaluates the economic, social, and cultural impacts of the festival on the local community and the region. Based on the analysis, a set of development strategies is formulated, integrating the research outcomes with theoretical frameworks. The strategies emphasize collaboration among local communities, governmental bodies, and tourism stakeholders. Validation of the strategies is conducted through focused group discussions involving relevant parties. The research concludes with recommendations for implementing the proposed strategies and underlines the importance of continuous evaluation and refinement based on evolving circumstances.Keywords: Development Strategy; Tourism; Culture; Local Wisdom